Are There Any Cognitive Benefits of Computer-Based Foreign Language Training for Healthy Elderly People? – A Mini-Review - Klimova, Blanka (Frontiers in Psychology, 2021)
The purpose of this mini-review is to investigate if there are any cognitive benefits of computer-based foreign language training for healthy older individuals aged 55+ years. The author conducted a literature search of peer-reviewed English written research articles found in Pub Med, Web of Science and Scopus. The findings of this mini-review reveal that the research on the cognitive benefits of computer-based foreign language training for healthy older individuals is small-scale. The limited research findings of only three relevant studies indicate that these computer-based foreign language training programs may bring cognitive benefits for healthy elderly people, especially as far as the enhancement of their cognitive functions such as working memory are concerned. In addition, the authors of these studies suggest that FLL is a useful activity for healthy older adults since it has the benefits of being meaningful (an advantage over other cognitive training approaches) and provides the chance for acquiring important skills that can benefit other aspects of life, such as travel or communication. In conclusion, the author of this mini-review also provides several implications for practice and future research.